152 “one to one: English for workplace communication course”: UMS administrative staff’s experience - Kamsilawati Kamlun; Priscilla Shak (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
Course attendees' feedback on what is necessary in a programme or course is vital for the ongoing development and betterment of a course. Against this context, this study discusses the degree to which the course goals are accomplished through the ‘One to One: English for Workplace Communication’ course. The main purpose of such feedback is to enhance the quality of the course and to provide direct feedback to the facilitators. To achieve this, the study focusses on the understanding of the administrative staff of the course material, which is important to their workplace needs for oral and written communication aspect. Via a reflective journal, a survey was collected using a qualitative approach from a group of administrative staff at Universiti Malaysia Sabah through a reflective journal as well as observation. The larger of these dealt with aspects of oral and written communication as well as the course’s overall reflection. The finding of the study discussed the input of the workers on the course 'One to One: English for Workplace Communication' and their experiences during the two-day course. These positively integrated conditions of learning may lead to productive performance, not only in the professional competence of learners, but may also affect their English proficiency.